Examining the Impact of Sharia Law on Apprenticeship Schemes and Child Rights in Northern Nigeria - Daniel Nte, Ngboawaji; Arifin Ridwan; Joda Adekunbi Omolara (Institut Agama Islam Negeri Metro, 2024)
This study examines the intersection of Sharia law, apprenticeship schemes, and child rights in Northern Nigeria, a region predominantly Muslim. Apprenticeship schemes are a vital means of economic empowerment and skill acquisition in areas marked by poverty. However, while these programs foster wealth creation, they also raise significant legal concerns regarding child labor, exploitation, and neglect. This research explores how Islamic education supports apprenticeship systems, while also addressing the legal and socio-cultural challenges related to child protection. Given the widespread reliance on apprenticeships in the region, the study is urgently needed to identify how current practices may undermine children's rights and to propose reforms. Drawing on existing literature and fieldwork, the study analyzes the tension between traditional practices and the growing demand for stronger protections for vulnerable children in Northern Nigeria. The paper contributes to the ongoing discourse by offering specific policy recommendations and strategies for community engagement, aimed at creating more sustainable and child-friendly apprenticeship systems.